PENGEMBANGAN MULTIMEDIA INTERAKTIF BERMUATAN MATERI MIKROBIOLOGI BERBASIS EDMODO ANDROID - Trio Ageng Prayitno; Nuril Hidayati (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2017)
A more interactive and fun microbiology learning solution by utilizing information technology is the development of interactive multimedia of microbiological material based on Edmodo Android. The purpose of this research is to produce interactive multimedia microbiology based on Edmodo Android. The research method used is research and development. Interactive multimedia microbiology based on Edmodo Android developed with Thiagarajan development model. The research is done through define stage, design stage, and develop stage. The data of the research are validation questionnaire from media experts, microbiology material experts, and practitioners. The research data is corrected by using the percentage of eligibility criteria.